Quasars as Cosmological Standard Candles - Negrete, C. Alenka; Dultzin, Deborah; Marziani, Paola; Sulentic, Jack W.; Esparza-Arredondo, Donají; Martínez-Aldama, Mary L.; Del Olmo, Ascensión (Frontiers in Astronomy and Space Sciences, 2017)
We propose the use of quasars with accretion rate near to Eddington ratio (extreme quasars) as standard candles. The selection criteria is based on the Eigenvector 1 (E1) formalism. Our first sample is a selection of 334 optical quasar spectra from the SDSS DR7 database with a S/N \gt\ 20. Using the E1, we define primary and secondary selection criteria in the optical spectral range. We show that it is possible to derive a redshift-independent estimate of luminosity for extreme Eddington ratio sources. Our results are consistent with concordance cosmology but we need to work with other spectral ranges to take into account the quasar orientation, among other constrains.